Multi-Response Optimization and Cell Structure-Property Relationships of Polylactide (PLA) Foams - Yudanto, Yusuf Arya; Petchsuk, Atitsa; Opaprakasit, Pakorn (Applied Science and Engineering Progress, 2024)
The renewability and ease of processing of polylactide (PLA) make it ideal for disposable foam products. However, controlling the foam structure is challenging due to its low melt strength and crystallization ability, which can result in cell rupture-prone and excessively large cells, necessitating a comprehensive understanding of the influences of foaming parameters (temperature, pressure, and time) on cell structures and properties to unlock PLA’s full potential. This study optimizes the fabrication of PLA foams using solid-state batch foaming under supercritical CO2 conditions by employing a central composite design of response surface methodology. Single-parameter investigations reveal that higher foaming temperature, increased pressure, and longer foaming time increase the apparent density due to reduced polymer viscosity, pressure-dependent gas entrapment, and enhanced gas diffusion, leading to faster cell nucleation and cell formation. The compressive properties depend on stress-strain behavior and cell morphology, influenced by the cell shape and wall thickness. Thicker cell walls delay cell buckling and improve compression resistance. Higher sphericality evenly distributes compressive stress across cell surfaces, enhancing the foam’s resilience against localized collapse. Multi-response optimization successfully fabricated lightweight PLA foam (0.134 g/cc apparent density) with enhanced compressive modulus (1.955 MPa at 50% strain) and controlled cell morphology (average cell size of 21.055 μm and cell density of 52.385 × 105 cells/cm3) at optimized foaming conditions (180 °C, 165 bar, and 2.3 h). The PLA foams have potential as a reusable and degradable absorbent for liquids and oils, but there are challenges in scaling production.